Anterior Cruciate Ligament Injury at the Time of Anterior Tibial Spine Fracture in Young Patients: An Observational Cohort Study. Issue 9 (October 2019) - Mayo, Meredith H.; Mitchell, Justin J.; Axibal, Derek P.; Chahla, Jorge; Palmer, Claire; Vidal, Armando F.; Rhodes, Jason T.
Abstract : Background: Anterior tibial spine fractures (ATSF) in the skeletally immature parallel anterior cruciate ligament (ACL) tears in adult patients, yet these injuries are generally regarded as mutually exclusive. Biomechanical analysis suggests that intrinsic ACL damage occurs during ATSF, and long-term clinical studies demonstrate residual anteroposterior knee laxity following ATSF. We aim to describe prevalence, demographics, and characteristics of pediatric patients who sustained ATSF with concomitant ACL injury. Methods: We included 129 patients with ATSF over a 16-year period. Age, sex, injury mechanism, ATSF type, magnetic resonance imaging (MRI) evaluation, treatment modality, ACL injury, and concomitant meniscal/chondral injuries were analyzed. Concurrent ACL injury was confirmed either from MRI or intraoperatively. Results: Nineteen percent (n=25) of ATSF patients had concomitant ACL injury, with ACL injury significantly more likely in type II or type III ATSF compared with type I ATSF ( P =0.03). Patients with combined ATSF/ACL injury were significantly older ( P =0.02) and more likely to be male ( P =0.01). Mechanism of ATSF injury was not associated with ACL injury ( P =0.83). Preoperative MRI had low sensitivity (0.09) for recognizing ACL injury at the time of ATSF relative to intraoperative assessment. Half of ATSF/ACL-injured patients had additional meniscal or chondral injury, with meniscal repair or debridement required in 37.5% of the type II ATSF/ACL injury. Conclusions: There are demographic characteristics, such as age (older) and sex (male), associated with a higher risk of concomitant ACL injury at the time of ATSF. Type II and type III ATSF patterns had a higher prevalence of ACL injury. MRI failed to correctly identify ACL injury at the time of ATSF. Concomitant ACL injury at the time of ATSF is highly prevalent in the skeletally immature, occurring in 19.4% of patients with ATSF. Level of Evidence: Level IV—case series.